Характеристика перинатальних наслідків розродження жінок з екстрагенітальною патологією, які пройшли етап санаторної реабілітації - Сюсюка, Володимир Григорович; Котлова, Юлія Валентинівна; Сюсюка, В. Г.; Котлова, Ю. В.; Syusyuka, V. G.; Kotlova, Yu. V. (My University, 2015)
Мета — дати оцінку стану новонароджених та перебігу їх раннього неонатального періоду, матері яких пройшли етап санаторного оздоровлення у зв'язку з екстрагенітальною патологією. Пацієнти та методи. Обстежено 127 вагітних терміном гестації 12–35 тижнів, які перебували на санаторному оздоровленні (санаторій «Великий Луг» м. Запоріжжя). Основну групу становили 97 вагітних з екстрагенітальною патологією. Групу контролю склали 30 соматично здорових вагітних, які проходили оздоровлення за акушерськими показаннями. Цель — дать оценку состоянию новорожденных и течения их раннего неонатального периода, матери которых прошли этап санаторного оздоровления в связи с экстрагенитальной патологией. Пациенты и методы. Обследовано 127 беременных сроком гестации 12–35 недель, которые находились на санаторном оздоровлении (санаторий «Великий Луг»). В основную группу включены 97 беременных с экстрагенитальной патологией. Группу контроля составили 30 соматически здоровых беременных, проходивших оздоровление в связи с акушерскими показаниями. Special perinatal pathologies characterized by diseases of mother very often occur in extragenital pathology (EGP) clinical picture. Increase of number of preg* nant women with associated EGP and available complications which are stipulated by EGP, on the one part, requires necessary complex treatment and, on the other part, it raises risk of polypragmasy. That is why use of medical, physical factors for pregnant women permits to limit quantity of therapeutic substances without decrease of the clinical effect and to reduce possibility of unfavorable influence of pharmacological drugs on fetus. Object of the work — is to estimate state of newborns and course of their early neonatal period, state of mothers who had a stage of sanatorium health improvement because of available extragenital pathology. Group оf examined persons and methods of investigation. There were examined 127 pregnant women with gestation term of 12–35 weeks who had under* gone sanatorium health improvement. Sanatorium health improvement was carried out in conditions of special department for pregnant women in Velikiy Lug sanatorium (Chief doctor is Shapran N.F.), Zaporizhzhia city, according to standards of sanatorium treatment [7, 8]. The main group comprised 97 pregnant women with EGP. Criterion for selection was hard somatic diseases. Control group consisted of 30 somatically healthy pregnant women. Average age of examined women in the main and control groups statistically (р < 0.05) was not different and made 28.7 ± 0.76 and 27.3 ± 1.54 years, correspondingly.
Характеристика перинатальных исходов родоразрешения женщин с экстрагенитальной патологией, которые прошли этап санаторной реабилитации
Characteristics of perinatal consequences after delivery for women with extragenital pathology who got a stage of sanatorium rehabilitation
Keywords: вагітність; екстрагенітальна патологія; психоемоційний стан; акушерські та перинатальні ускладнення; беременность; экстрагенитальная патология; психоэмоциональное состояние; акушерские и перинатальные осложнения; pregnancy; extragenital pathology; emotional state; obstetric and perinatal complications